2021
DOI: 10.58258/jime.v7i4.2462
|View full text |Cite
|
Sign up to set email alerts
|

Analisis Kesulitan Guru Dalam Menyusun Perangkat Pembelajaran Di SDN 32 Cakranegara Tahun Ajaran 2020/2021

Abstract: This study aims to describe the difficulties experienced by teacher in Analysis of Teacher Difficulties in Preparing the Learning Equipments in SD Negeri 32 Cakranegara for the 2020/2021 Academic Year. The aims of this research are to describe the difficulties of teachers in learning plan and to describe the difficulties of teachers in learning implementing. The aims of this research also to describe the difficulties of teachers in learning evaluating at SD Negeri 32 Cakranegara for the 2020/2021 Academic Year… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 0 publications
0
2
0
Order By: Relevance
“…This aligns with the research finding from Wahidmurni et al (2021), which stated that teachers' inability to design HOTS-oriented questions stemmed from their difficulty in transforming action verbs within the basic competencies into relevant competency achievement indicators. Similarly, Kurnia et al, (2021) indicated that teachers struggled in developing competency achievement indicators and learning objectives due to their limited ability to analyze the cognitive levels within competency standards and basic competencies, which served as the foundation for elaborating competency achievement indicators and learning objectives. Teachers tended to rely more on examples of lesson plans found on the internet without critically analyzing their authenticity or applicability.…”
Section: Their Geographical Condition Accuratelymentioning
confidence: 99%
See 1 more Smart Citation
“…This aligns with the research finding from Wahidmurni et al (2021), which stated that teachers' inability to design HOTS-oriented questions stemmed from their difficulty in transforming action verbs within the basic competencies into relevant competency achievement indicators. Similarly, Kurnia et al, (2021) indicated that teachers struggled in developing competency achievement indicators and learning objectives due to their limited ability to analyze the cognitive levels within competency standards and basic competencies, which served as the foundation for elaborating competency achievement indicators and learning objectives. Teachers tended to rely more on examples of lesson plans found on the internet without critically analyzing their authenticity or applicability.…”
Section: Their Geographical Condition Accuratelymentioning
confidence: 99%
“…This situation aligns with the conclusions of Ngaziah et al, (2021), who emphasized that teachers exhibited unsatisfactory pedagogical competence in the field of online learning, particularly in the areas of conducting learning outcome assessments and evaluating instructional materials. Kurnia et al, (2021) discovered various challenges encountered by primary school teachers in developing assessment tools are due to difficulties in (1) aligning basic competencies, indicators, and materials, (2) matching questions with basic competencies, indicators, and materials, (3) creating multiple-choice questions, essay questions, true-false questions, matching questions, and fill-in-the-blank questions, and (4) designing attitude assessments and skill assessments. This suggests a link between the difficulties teachers encounter when developing competence achievement indicators in learning objectives and their ability to generate relevant assessment questions or instruments.…”
Section: Distinguish Between Uppercase and Lowercase Lettersmentioning
confidence: 99%